Faktor Penyebab Terjadinya Diparias Pidana terhadap Penyalahguna Narkotika di Pengadilan Negeri Bengkulu - Herlita Eryke (University Of Bengkulu Law Journal, 2022)
Drugs addict are self-victimizing victims, namely victims and perpetrators of crimes theycommit themselves. The criminal character of a drug addict is a person who is physically'sick.' One of the parties with a very significant task in the criminal justice system is the judge.Judges have an essential role in determining the 'fate' of drugs addict in the future. Incriminal decisions, which can be seen from the registration of cases at the Bengkulu DistrictCourt for narcotics abusers, there are many disparities in the verdicts for drugs addict. Somewere sentenced to 5 years, two years, one year, eight months, and six months, and some wereonly sentenced to rehabilitation. The differences in the sentencing of different judges raisesignificant questions for justice seekers and the general public. Why is it like that? This studyaims to describe the factors that cause criminal disparities for drugs addict. This researchuses socio-legal research methods by collecting data and information and facts from thesymptoms in the field, either through observation, interviews, and documentation. The datawas collected in the form of primary and secondary data, which were selected purposivelyaccording to the characteristics of the data. Data analysis was carried out descriptively withinductive and deductive approaches. As for the study results, the factors that became criminaldisparities were: facts revealed in court, criminal acts, evidence found at the case scene,demands of the public prosecutor, aggravating and mitigating matters, and criminalprovisions violated.